Randomized, double-blind, placebo-controlled split-face trial of the efficacy of tranexamic acid by drug delivery through microneedling in the treatment of melasma - Kuster Kaminski Arida, Dâmia; Orso Rebellato, Priscila Regina; Marioto de Campos, Giovana Liz; Costa, Adriane; Vilaverde Schmitt, Juliano [UNESP]; Larocca Skare, Thelma; Rodrigues Lisboa Faucz, Luciana (Wiley, 2021)
Background: Melasma is a prevalent skin pigmentation disorder that is difficult to treat. Tranexamic acid (TA) is a potential agent, but there are few studies on its effectiveness under the transdermal route (drug delivery—Dd). One of these Dd pathways is through microneedling, which seems to be effective itself. Objective: To evaluate the efficacy of tranexamic acid when applied in the form of drug delivery through microneedling in the treatment of facial melasma. Methods: A randomized controlled double-blind split-face trial with 3 monthly sessions in 20 melasma patients: microneedling was performed in the entire face, and then TA solution was applied to one hemiface and placebo to the other. The effectiveness was measured using Hemi-MASI (Melasma Area and Severity Index), images pixels, and perceptions of experts and patients. Results: Hemi-MASI regressed 22% in control and 29% in TA side. A good/better improvement was found in 37.5% of the control and 42.5% of TA by the experts and 60% of the patients for both sides. Pixels increased by 5 and 7, respectively. In none of these criteria, there was a significant difference between the sides. Conclusion: Tranexamic acid in drug delivery through microneedling did not bring additional benefit to the treatment of melisma.
Keywords: drug delivery; melasma; microneedling; randomized controlled trial; tranexamic acid